Determinants of Decision to Pay a Price Premium for Modified Food in Korea - Kaya, Ozgur (2013)
The knowledge of whether or not consumers are willing to pay a price premiums and the amount of the willingness to pay (WTP) when buying foods with more fiber, vitamins, protein, fat, and less saturated fat shapes food manufacturer and distributor marketing strategies and supports the development of public health programs. In this study we analyze survey data collected in Korea to identify consumer profiles associated with both the binary decision and the level of WTP for foods with nutritionally desired attributes. Results indicate the importance of socio-economic variables, location, variables representing the risk of health problems, implicit lifestyle differences and attributes related to food preparation. [EconLit Classification: Q130, Q180].